Stakeholder Collaboration in Sustainable Tourism Development in Banyuwangi Regency - Arief Rahman; Indrianawati Usman; Mohammad Eri Irawan (Magister Administrasi Publik, 2022)
This research is based on developments in the tourism sector in Banyuwangi District. This case study is based on a qualitative research design. The objective of this study aimed to assess and evaluate the efforts of Banyuwangi District Government in managing the complexity of stakeholders’ interests in local tourism destinations. The study was underpinned by the stakeholder theory and collaboration theory and how their relevance in developing tourism destinations within the context of sustainable tourism. Based on the two theories, the existence of local governments is considered an important component of stakeholder space as well as the coordinator and manager of the collaboration. The study collected data from 17 informants who comprised the Banyuwangi Regent, Banyuwangi District Government, Ministry of Tourism, Tourism Association, DPRD, Community, Media, Travel awareness group, Academics, and Tourism Industry. Research results showed that tourism is a strategic sector in regional, regional and national economic development. However, the tourism industry is also known to be very complex, fragmented, and involves various interested parties. The complexity of challenges faced in tourist destination management includes planning, organizing, managing, and controlling. Therefore, cooperation, coordination, and communication among stakeholders, as well as the involvement of the government at all levels, the private sector, and also the local community are crucial.